Knowledge about Hiv/Aids among Drivers in Birgunj Bus Park: A Descriptive Analysis - Patel, Shambhu Prasad (Academic Voices: A Multidisciplinary Journal, 2014)
<!--[if gte mso 9]> <![endif]--> One of the growing epidemics in the world today is HIV/AIDS. In the cities with high mobility, bus drivers are considered as the risk group for HIV/AIDS. Most of these younger people do not have access to information, condoms, supportive services which enable them to have safer sex. A descriptive cross sectional study was done to access knowledge about HIV/AIDS among drivers of Birgunj Bus Park. The analysis of the data revealed that majority of the respondents were between ages 20-24 years; have heard from media (radio, Television and newspapers); unsafe sex is the means of transmission and using condom during sexual intercourse can prevent HIV/AIDS. The present study strongly recommends that there is immediate need of program to create awareness among drivers including co-workers, vulnerable youths and other high risk groups such as migrant populations. Academic Voices, Vol. 3, No. 1, 2013, Pages 50-53 DOI: http://dx.doi.org/10.3126/av.v3i1.9589 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-ansi-language:EN-US; mso-fareast-language:EN-US;} --> <!--[endif] -->